Fatal Hemoptysis due to Chronic Cavitary Pulmonary Aspergillosis Complicated by Nontuberculous Mycobacterial Tuberculosis - Ioannis Kokkonouzis; Ioannis Athanasopoulos; Nikolaos Doulgerakis; Grigorios Tsonis; Ioannis Lampaditis; Nikolaos Saridis; Vasilios Skoufaras (Case Reports in Infectious Diseases)
A 51-year-old man, with a history of severe COPD and bilateral pneumothorax, who was under treatment for pulmonary tuberculosis due to mycobacterium avium, was admitted due to high-grade fever, weight loss, cough, and production of purulent sputum, for almost one month without any special improvement despite adequate antibiotics treatment in outpatient setting. A CT scan revealed multiple consolidations, fibrosis, scaring, and cavitary lesions in both upper lobes with newly shadows which were fungus balls inside them. Aspergillus flavius was isolated in three sputum samples, a diagnosis of chronic cavitary pulmonary aspergillosis was made, and treatment with intravenous amphotericin B was started. An initially clinical improvement was noted, and a first episode of minor hemoptysis was treated with conservative measures. Unfortunately a second major episode of hemoptysis occurred and he died almost immediately. Aspergilloma is defined as the presence of a fungus ball inside a preexisting pulmonary cavity or dilated airway and is one of the clinical conditions associated with the clinical spectrum of pulmonary colonization. Tuberculosis is the most common underling disease. Hemoptysis is the most common symptom. Antifungal antibiotics, surgical interventions, bronchial arteries embolization, and intracavity infusion of antibiotics have been proposed without always adequate sufficiency.